'A small, fierce being': Jon Silkin, Isaac Rosenberg, and the definition of the Anglo-Jewish poet. Issue 5 (4th May 2022) - Copley, Hannah
ABSTRACT: Despite being 'one of the most distinctive and distinguished of those British poets who began to publish in the 1950s', the writer, editor, critic, and translator Jon Silkin remains a largely forgotten figure in contemporary poetry. However, with the publication his Complete Poems in 2015 and the availability of his archive, there has been a renewed critical interest in the charismatic, prolific, and contentious poet. Drawing heavily from Silkin's unpublished correspondence, this article contributes to this revival by exploring his place within the post-1945 Anglo-Jewish community and his relationship to his Jewish identity and cultural heritage. In particular, it investigates how the First World War poet (and fellow Anglo-Jew) Isaac Rosenberg became a vital means through which Silkin articulated his poetic identity as one caught between two hyphenated cultures and histories and defined his relationship with his Anglo-Jewish contemporaries.